THE EFFECT OF SPECIFIC EXERCISES UNDER COMPETITIVE PRESSURE ON DEVELOPING THE ELEMENTS OF AGILITY, MUSCULAR STRENGTH AND THE LEVEL OF COMPLEX SKILL PERFORMANCE FOR JUNIOR HANDBALL PLAYERS - Jaber, Mortada Baha Nasser; Chaloub, Haider Abdulwahid (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The importance of the research lies in using a training method that depends on simulating the reality of the game, and this is done by preparing specific exercises that include playing positions and in the presence of defensive players and according to the training goal and playing areas, whether from the corners or the middle of the game, and each player must perform the exercise with strength and speed similar to the performance during the game to bring players reach high levels agility, muscle power and complex skill performance throughout the match. As for the research problem: Through the researchers' Observation and field experiences in the game, they found that there are many mistakes made by players during the required motor performance for offensive skills and under opposing pressure, in addition to slowness and lack of movement and dealing with the ball or without it during defensive pressure, which negatively affects the result of the match. Therefore, researchers tried to study this problem by finding solutions to it by putting specific exercises under opposing pressure to raise the level of agility and muscle power and complex offensive skill performance for junior handball players. The study aimed Well: Effect specific exercises under opposing pressure in developing the elements of agility and muscle power and the level of complex skill performance for junior handball players. As for the research hypothesis: The qualitative Have practice a significant Influenced by developing the elements of agility and muscle power and the level of complex skill performance for junior handball players. As for the research methodology: The researchers used experimental methods two equivalent groups (control and experimental) with pre- and post-tests to suit the research objectives. As for Research Group and its sample, they were chosen intentionally, and they are players in the professional center are interconnected with the Najaf Governorate, numbering (24) players, and (16) players were chosen from them and randomly divided (by drawing lots) into two groups (control group and experimental group), each group has (8) players.